Pedagogías Alternativas, paz y discursos de odio (Memorias Sifored - Encuentros Educación UAN, 2023)
The objective of this research is to achieve critical analyzes in the 9th grade students of the Gustavo Restrepo school for the construction of peace in the face of hate speech that is generated on social networks. The main problem is marked in the reproduction of said discourses in school and training processes that do not allow achieving the objective. A workshop on social networks was held for the students, where some controversial phrases were raised about different content creators, establishingdebates around these speeches. As a result, each student's perspective varies depending on their social and cultural context, causing disputes and fragmentation in interpersonal relationships.
Keywords: ICT; Pedagogy; peace; School; social media